2009
DOI: 10.1111/j.1753-6405.2009.00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges, lessons learned and results following the implementation of a human papilloma virus school vaccination program in South Australia

Abstract: Objective: To describe the process and challenges in the roll out of a large cervical cancer vaccination program to protect against human papilloma virus (HPV) infection. Methods: This article describes the process of planning and implementing a HPV vaccination program using the existing state‐wide framework that supports vaccine delivery to all 219 high schools in South Australia. The decision was made to offer three doses of HPV vaccine to 50,191 female students in Years 8‐12 during the 2007 school year.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 5 publications
2
50
0
Order By: Relevance
“…9,[23][24][25][26] However, this study clearly shows that a range of HPV vaccine delivery strategies can be successful in low-resource settings. The coverage levels achieved resemble those obtained with vaccination programmes in high-income countries: 65.1% uptake of the first dose in British Columbia, Canada; 27 68.5% uptake of two doses in Manchester, United Kingdom; 28 and 26.7% and 55.0% coverage with three doses in the United States 29 and southern Australia, 30 respectively. Although our study involved demonstration projects, admittedly not reflective of routine field conditions, HPV vaccination was conducted in large, geographically distinct areas using only the infrastructure already in place for the EPI.…”
Section: Discussionmentioning
confidence: 58%
“…9,[23][24][25][26] However, this study clearly shows that a range of HPV vaccine delivery strategies can be successful in low-resource settings. The coverage levels achieved resemble those obtained with vaccination programmes in high-income countries: 65.1% uptake of the first dose in British Columbia, Canada; 27 68.5% uptake of two doses in Manchester, United Kingdom; 28 and 26.7% and 55.0% coverage with three doses in the United States 29 and southern Australia, 30 respectively. Although our study involved demonstration projects, admittedly not reflective of routine field conditions, HPV vaccination was conducted in large, geographically distinct areas using only the infrastructure already in place for the EPI.…”
Section: Discussionmentioning
confidence: 58%
“…A similar observation was made following the introduction of HPV vaccine in South Australia, with significantly lower HBV uptake. 53 The potential for poor acceptance for one vaccine to affect uptake of a co-administered vaccine in our SIC is concerning and requires ongoing research.…”
Section: Selective Immunization Schedulesmentioning
confidence: 99%
“…Some countries within the Gardasil Access Program used schools and clinics and vaccination based on school-based, health facilitybased, and mixed strategies (Lander et al, 2012). Some of the national programs (TNSCCS, 2007;Ogilvie et al, 2010;Limia and Pachon, 2011;Binagwaho et al, 2012) and regional level programs (Brabin et al, 2008;Watson et al, 2009) indicated efficient vaccination to prevent cervical cancer through a national media campaign. In Turkey, the routine screening program for cervical cancer started with the "National Standards for Cervical Cancer Screening" published in 2007.…”
Section: Hpv Vaccine Programsmentioning
confidence: 99%